Determinants of crescent kick performance in pencak silat athletes: path analysis - Jhovan Saputra; Nurul Ihsan; Anton Komaini; Eval Edmizal (Global Econedu, 2026)
This study aimed to examine the direct and indirect effects of speed, flexibility, and training motivation on crescent kick ability among Pencak Silat athletes at Walet Puti Martial Arts School, Jambi City. A quantitative associative design with path analysis was employed. The sample consisted of 40 athletes selected through purposive sampling from a population of 80 athletes. Speed was measured using a 30-meter sprint test, flexibility through the sit-and-reach test, motivation using a validated questionnaire, and crescent kick ability through a standardized crescent kick test. Data were analyzed using path analysis at a significance level of 0.05. Speed demonstrated the strongest direct effect on crescent kick ability (β = -0.934; 87.20%), followed by flexibility (β = 0.292; 0.85%) and motivation (β = 0.091; 0.82%). Motivation mediated the effects of speed (0.25%) and flexibility (0.15%) on kicking performance. Simultaneously, speed, flexibility, and motivation explained 96.82% of the variance in crescent kick ability (R² = 0.984). Speed was the dominant determinant of crescent kick performance, while flexibility and motivation provided complementary contributions. Integrating physical and psychological training is essential for optimizing Pencak Silat performance.